Does Vitamin D3 supplementation improve Depression scores among rural adolescent? A Cluster Randomized control trial - P. T. Satyanarayana; R. Suryanarayana; S. TY; S. Reddy; N. AG (European Psychiatry, 2023)
Introduction Contemporary evidence has established that stunted vitamin D levels are associated with depression, poor mood and other mental disorders.Vitamin D supplementation might play a significant role in depression. Objectives To assess the role of supplementation of Vitamin D on depression scores among rural adolescents Methods It is a Cluster Randomized Control Trial carried out for a period of two years. 10 Government rural schools were taken as clusters and sample size was calculated using previous literature.(Libuda.et al:EJN. 2020; 27:1-0) 150 was the final sample size in each group. Adolescents aged 11-18 years were included and with any pre-existing mental health illness, renal abnormalities and confirmed neurological disorders (Epilepsy) were excluded. Intervention group received 2 months of 2000 IU per day for 9 weeks and Control arm received 500 mg of Calcium and low dose (250 IU) of Vitamin D. To assess socio-demographic status a pretested semi structured questionnaire was used. To assess depression, Becks Depression Inventory (BDI-II) was used. Venous Blood was taken by experienced lab technician and analyzed in Central Diagnostic Laboratory Services, Biochemistry Department, SDUMC, SDUAHER, Kolar, Karnataka, India. Study was started after Central ethics Committee approval. This study is intramural funded project (Rs.6,12,000/). Clinical Trials Registry number: CTRI/2021/07/034654: REF/2021/03/042355. All the data collected entered in Microsoft excel and analysed using SPSS v 22(IBM corp,USA). Pre-intervention and post intervention difference assessed with t-test summarized as Mean and Standard deviation (SD) with statistically significant difference defined with p value less than 0.05. Both Intention-To-Treat analysis and Per Protocol analysis done and reported separately. Results